2009
DOI: 10.1039/b912684h
|View full text |Cite
|
Sign up to set email alerts
|

Hydration structures of 2′-deoxyguanosine studied by IR-UV double resonance spectroscopy: comparison with guanosine

Abstract: Infrared spectra of mono- and dihydrated clusters of 2'-deoxyguanosine (2'-dGs), which are formed by laser desorption combined with supersonic jet-cooling, have been measured by the technique of IR-UV double resonance spectroscopy. The structures of these hydrates are compared with those reported for guanosine (Gs) to elucidate the importance of the 2'-hydroxy group in the hydration. It is shown that monohydrated structures observed for 2'-dGs are similar to those of Gs, indicating no significant influence by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…By controlling the source conditions, it is also possible to generate clusters of desorbed molecules with each other or with water molecules to mimic base pairs and microsolvation. [65][66][67][68][69][70][71][72] Downstream, the jet cooled molecules are excited and photo-ionized and the ions are detected in a time-of-flight mass spectrometer. 64,[73][74] Figure 2 shows a schematic overview of the most common laser spectroscopy approaches to studying neutral molecules in the gas phase.…”
Section: Techniquesmentioning
confidence: 99%
“…By controlling the source conditions, it is also possible to generate clusters of desorbed molecules with each other or with water molecules to mimic base pairs and microsolvation. [65][66][67][68][69][70][71][72] Downstream, the jet cooled molecules are excited and photo-ionized and the ions are detected in a time-of-flight mass spectrometer. 64,[73][74] Figure 2 shows a schematic overview of the most common laser spectroscopy approaches to studying neutral molecules in the gas phase.…”
Section: Techniquesmentioning
confidence: 99%
“…In our previous studies, 2,3 we have investigated hydrated clusters of guanosine and 2 0 -deoxyguanosine and found that the presence of the sugar group leads to the stabilization of specific hydration structures. Furthermore, the keto-enol tautomerization and excited-state dynamics of these nucleosides are significantly influenced by the hydration.…”
Section: Introductionmentioning
confidence: 99%
“…Thus dG •+ and Gs •+ , formed either in the source or from the [Cu II dG 3 ] 2+ and [Cu II Gs 3 ] 2+ precursor complexes, have different structures to those formed from the dimer radical cations. Although this appears to be a novel finding in terms of tautomerisation within gas-phase supramolecular complexes, a search of the literature reveals examples of different gas-phase tautomeric forms of neutral dG and Gs that arise from the way that they are generated in the gas-phase [40][41][42]. Thus IR spectroscopy with resonant two-photon ionisation has been used to show that neutral dG and Gs formed via laser desorption exist in the enol forms D1 and D2 [40], but when hydrated by one or two water molecules, exist in the keto forms C1 and C2 [41,42].…”
Section: Do the Dimeric Radical Cations Have A Unique Structure Contamentioning
confidence: 95%
“…Although this appears to be a novel finding in terms of tautomerisation within gas-phase supramolecular complexes, a search of the literature reveals examples of different gas-phase tautomeric forms of neutral dG and Gs that arise from the way that they are generated in the gas-phase [40][41][42]. Thus IR spectroscopy with resonant two-photon ionisation has been used to show that neutral dG and Gs formed via laser desorption exist in the enol forms D1 and D2 [40], but when hydrated by one or two water molecules, exist in the keto forms C1 and C2 [41,42]. It is also worth mentioning that CID of metal complexes of amino acids and peptides can give rises to isomeric radical cations that depend on the metal complex [43][44][45].…”
Section: Do the Dimeric Radical Cations Have A Unique Structure Contamentioning
confidence: 95%